Analysis of Android-Based Educational Game Media Development Needs for Social Studies Learning in Elementary Schools - Elvani Hertati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
This study aims to find out information about the need for educational games, perceptions of educational games, and educational game design according to teachers and students. The method used in this research is a survey to find out the initial data which is the process of developing educational game products. The instrument used is a questionnaire sheet and an interview sheet. The data analysis technique used quantitative and qualitative descriptive statistical analysis techniques. The schools that were used as research samples were 3 schools spread across Magelang Regency. Each school selected 2 class teachers. The results showed that teachers and students at SD Magelang Regency had a good perception of educational games. The need for educational games according to the teacher is a game that contains evaluation questions and the type of game that students need is an adventure genre game. The design of educational games developed according to the teacher must pay attention to aspects of appearance, content, and affordability of the game. Meanwhile, according to students, educational games are games that are interesting and have challenges or missions that must be completed.